Are we curing one evil with another? A translational approach targeting the role of neoatherosclerosis in late stent failure. (29th April 2020) - Lenz, Tobias; Nicol, Philipp; Castellanos, Maria Isabel; Abdelgalil, Ayat Aboutaleb Abdellah; Hoppmann, Petra; Kempf, Wolfgang; Koppara, Tobias; Lahmann, Anna Lena; Rüscher, Alena; Kessler, Horst; Joner, Michael
Abstract: Neoatherosclerosis is defined as foamy macrophage infiltration into the peri-strut or neointimal area after stent implantation, potentially leading to late stent failure through progressive atherosclerotic changes including calcification, fibroatheroma, thin-cap fibroatheroma, and rupture with stent thrombosis (ST) in advanced stages. Human autopsy as well as intravascular imaging studies have led to the understanding of neoatherosclerosis formation as a similar but significantly accelerated pathophysiology as compared to native atherosclerosis. This acceleration is mainly based on disrupted endothelial integrity with insufficient barrier function and augmented transmigration of lipids following vascular injury after coronary intervention and especially after implantation of drug-eluting stents. In this review, we summarize translational insights into disease pathophysiology and discuss therapeutic approaches to tackle this novel disease entity. We introduce a novel animal model of neoatherosclerosis alongside accompanying in vitro experiments, which show impaired endothelial integrity causing increased permeability for low-density lipoprotein cholesterol resulting in foam cell transformation of human monocytes. In addition, we discuss novel intravascular imaging surrogates to improve reliable diagnosis of early stage neoatherosclerosis. Finally, a therapeutic approach to prevent in-stent neoatherosclerosis with magnesium-based bioresorbable scaffolds and systemic statin treatment demonstrated the potential to improve arterial healing and re-endothelialization, leading to significantly mitigated neoatherosclerosis formation in an animal model of neoatherosclerosis.